2019
DOI: 10.1007/s12571-019-00933-y
|View full text |Cite
|
Sign up to set email alerts
|

Food security and the functioning of wheat markets in Eurasia: a comparative price transmission analysis for the countries of Central Asia and the South Caucasus

Abstract: We investigated wheat price relationships between the import-dependent countries in Central Asia and the South Caucasus and the Black Sea wheat exporters to assess wheat market efficiency. This is crucial for ensuring availability and access to wheat and for reducing food insecurity. Results from linear and threshold error correction models suggested a strong influence of trade costs on market integration in Central Asia, while those costs were of minor importance in the South Caucasus. In particular, wheat tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Crop producers may benefit from the investment in grain market infrastructure, subsidized loans, and export insurance programs. These measures correlate with the recommendation of Svanidze et al [150] to complement trade and infrastructure-enhancing policies with the support of domestic producers in order to bring more stability to value chains in crop production. The establishment of tax incentives along with the allocation of preferential credits for agribusiness are recommended by Pirmatov et al [38] among the measures to support competitive advantages.…”
Section: Matching 3: Sustainability Of Agricultural Value Chains and supporting
confidence: 67%
“…Crop producers may benefit from the investment in grain market infrastructure, subsidized loans, and export insurance programs. These measures correlate with the recommendation of Svanidze et al [150] to complement trade and infrastructure-enhancing policies with the support of domestic producers in order to bring more stability to value chains in crop production. The establishment of tax incentives along with the allocation of preferential credits for agribusiness are recommended by Pirmatov et al [38] among the measures to support competitive advantages.…”
Section: Matching 3: Sustainability Of Agricultural Value Chains and supporting
confidence: 67%
“…Self-production and imports are methods for filling domestic food needs. Reliance solely upon imported food presents a big problem in the future; as food prices increase globally, middle-and low-income countries will be increasingly unable to afford to buy food from other countries (Funk and Brown, 2009), leading to steep domestic food prices caused by heavily imported food (Svanidze et al, 2019). Although food security is in a race against population growth, Grote (2014) and Goyal (2012) showed that population pressure, poverty, land degradation, and unstable environments had pushed food security further out of reach.…”
Section: Food Security In Indonesia 41 An Overviewmentioning
confidence: 99%
“…Supply-chain problems affect the market system and food price (Tadesse et al, 2014). The market needs to be monitored to control food prices and keep food accessible for all people; in other words, to reach food security (Svanidze et al, 2019). Figure 5 shows fluctuations in the price of rice in Indonesia during the pandemic.…”
Section: Food Security Post-covid-19mentioning
confidence: 99%
“…According to the study, in order to secure ghee food and to meet the needs of people in these countries, the market infrastructure should be developed, the unofficial payments should be eliminated, and the geopolitical conflicts should be resolved. Thus, the trade-enhancing policies should be linked to wheat sufficiency policies so that food security may improve (Svanidze et al, 2019). Another research examined the four major pillars that might affect food security: the availability of food, the access to it, its utilisation and the stability of food.…”
Section: Literature Reviewmentioning
confidence: 99%